Physical and biogeochemical properties of seasonal sea ice in the Atlantic sector of the Antarctic marginal ice zone - Audh, Riesna Reuben (Department of Oceanography, 2025)
The study of Antarctic sea ice biogeochemistry has largely focused on samples collected from pack ice during summer, with few winter data available. Measurements from the Antarctic marginal ice zone (AMIZ) have proven even more difficult to obtain. The AMIZ is a broad, circumpolar feature of the Southern Ocean where sea ice begins to form during winter. The incorporation of seawater during sea-ice growth along with chemical and biological processes operating within the ice results in a complex biogeochemical environment within the sea ice matrix. This thesis presents the first biogeochemical datasets for sea ice collected in the Atlantic AMIZ during winter and spring, including measurements from young pancake ice, consolidated first-year ice and brash ice. It also proposes a revised set of standard operating procedures for conducting interdisciplinary sampling in complex marginal ice conditions. Measurements of sea-ice temperature, salinity, crystal structure, δ O18 , chlorophyll and nutrient concentrations were combined with model simulations to decipher the conditions under which the ice formed and grew, how these conditions influenced the subsequent biogeochemical environment and how the sea-ice properties evolved from winter to spring. Our findings confirm that winter sea ice is biologically active and further suggest that the growth of sea ice in the AMIZ is not a linear progression of thickness with habitat space reduction as sea ice consolidates. Instead, sea ice consolidates and thickens as a result of multiple cycles of breaking and rafting of young ice, and the biogeochemical signatures of the young ice are conserved in the reformed, consolidated ice cover. Novel nitrate and particle δ N15 measurements enabled us to investigate the seasonal evolution of sea-ice nitrogen cycle dynamics in the AMIZ, revealing that processes such as nitrate assimilation and nitrification are ongoing during winter. A comparison of our data to previous studies suggests a temporally advanced nitrogen cycle compared to pack ice in the region. Finally, the first measurements of winter pancake ice and spring brash ice biogeochemistry are highlighted and illustrate the seasonal influence on the sea ice environment and surface ocean in the AMIZ. The work detailed in this thesis significantly advances the available data and knowledge base for the AMIZ, particularly related to the biogeochemistry of sea ice, and will help to improve and validate future modelling efforts by providing observations in a severely understudied region.